Clinical and epidemiological characteristics of measles in adults residents of the Altai territory - I. P. Saldan; N. V. Karbysheva; E. A. Bobrovsky; M. A. Nikonorova; I. G. Pashchenko; O. V. Beskhlebova; I. N. Kiushkina; U. V. Kalinina (Журнал инфектологии, 2019)
The aim of the study is to determine the clinical and epidemiological features of measles in the Altai territory. Materials and methods: a retrospective analysis of 92 medical histories of inpatient patients with a confirmed diagnosis of «Measles» at the age of 17 to 54 years, who were treated in the Infectious Departments of City Hospitals № 5 and №11 in Barnaul in 2015–2018, was made. Results: the epidemic situation of measles in the Altai territory is characterized by an increase of morbidity rate in 2015, as well as isolated cases in 2017–2018. The peculiarity of the outbreak of the disease was in-hospital infection of patients upon admission to medical hospitals and late diagnosis of measles, as well as the importation of infection from adjacent territories (regions of Russia and the Republic of Kazakhstan), which is confirmed by genotyping of the virus in patients. The development of the disease in 23,9% of those,who were vaccinated, was routinely observed in the age group older than 30 years. In the clinical picture of measles at the present stage, along with the classical manifestations, in 15.2% of patients in the first days of the disease gastroenteritis was marked, in 40,2% of patients the signs of hepatitis (cytolysis syndrome) were observed. Conclusion: the prevalence among the patientspersons, older than 30 years, may indicate the extinction of post-vaccination immunity. Timely immunization against measles in adulthood (after 30 years), will increase the effectiveness of measures to implement the program of elimination of measles in the Altai territory. The development of gastroenteritis up to the 5 days of the disease (on average 2,5±0.9 days), hepatitis in the period of height of the disease (in 15,2% and 40,2% of patients, respectively), determined the erroneous diagnosis of «Enterovirus infection», pseudotuberculosis, etc. and deserved the attention of practitioners.